Immigration and the Ambivalence of the School: Between Inclusion and Exclusion of Migrant Youth. (November 2019) - Ribeiro, Norberto; Malafaia, Carla; Neves, Tiago; Menezes, Isabel
This article examines the perceptions of young migrants (and non-migrants), their parents, and teachers to discuss whether the school is a device of inclusion or a device of exclusion that produces inequalities. It presents qualitative and quantitative data collected in the urban areas of Lisbon and Porto. First, we analyze data from 14 focus groups, involving 94 participants, and 12 interviews. Second, we consider survey data from a sample of 1, 010 youngsters of Portuguese, Angolan, and Brazilian origin. Findings suggest the school plays an ambivalent role; however, participants emphasize mostly its discriminatory and segregating role.